FORMULATION AND CHARACTERIZATION OF BETULIN-LOADED MICROEMULSION FOR ANTI-GOUT THERAPY - SWATI BHASKARRAO SURDKAR; NAGARAJU BANDARU (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The study aimed to formulate and evaluate a betulin-loaded microemulsion for enhanced topical anti-gout efficacy and skin retention, using diclofenac diethylamine emulgel 1% as the positive control. Methods: Betulin microemulsions were prepared using medium-chain triglyceride oil, Tween 80, and ethanol through the phase inversion method. Physicochemical characterization was performed through droplet size analysis, zeta potential, viscosity, pH, and Fourier-transform infrared spectroscopy studies. Pseudo-ternary phase diagrams were constructed to optimize composition. Ex vivo permeation and skin retention were assessed using porcine skin in Franz diffusion cells, followed by skin homogenization and extraction. Anti-inflammatory efficacy was evaluated in a monosodium urate (MSU) crystal-induced gouty arthritis model in mice, while skin irritation studies were conducted in guinea pigs. Statistical analysis was performed using one-way analysis of variance followed by Dunnett’s test. Results: The optimized microemulsion (10% oil, 20% surfactant, 10% co-surfactant, and 0.5% betulin) exhibited droplet size of 152±3.4 nm, polydispersity index of 0.218, and zeta potential of –28.5 mV. Ex vivo studies revealed cumulative permeation of 50.2±3.0 μg/cm2 at 24 h with 24.7±2.3% retention in the skin. In vivo, betulin microemulsion (1%) significantly reduced paw edema and pro-inflammatory cytokines (interleukin-1 beta and tumor necrosis factor-alpha), and improved weight-bearing distribution compared to the MSU group (***p<0.001), demonstrating efficacy comparable to diclofenac emulgel. No dermal irritation was observed in guinea pigs. Conclusion: Betulin microemulsion exhibited favorable physicochemical properties, high skin retention, and potent topical anti-inflammatory activity in gout, with excellent dermal safety. These findings support its potential as a safe and effective topical delivery system for the management of gouty arthritis.